1998
DOI: 10.1103/physrevlett.80.197
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and Information in Neural Spike Trains

Abstract: The nervous system represents time dependent signals in sequences of discrete, identical action potentials or spikes; information is carried only in the spike arrival times. We show how to quantify this information, in bits, free from any assumptions about which features of the spike train or input signal are most important, and we apply this approach to the analysis of experiments on a motion sensitive neuron in the fly visual system. This neuron transmits information about the visual stimulus at rates of up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
1,038
1
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 869 publications
(1,063 citation statements)
references
References 20 publications
(19 reference statements)
15
1,038
1
9
Order By: Relevance
“…This is in contrast to the emphasis usually put on the spike train distances. In particular, the use of a metric specific for point processes like the Victor distance (Victor and Purpura, 1996) or a metric in an Euclidean space like for the binning distances is not so determinant for the discrimination performance as the classifier, given that in this case the binning procedure is not used to construct a high-dimensional space for the probability distributions (Strong et al, 1998). Notice that here we restricted ourselves to the type of classifier originally proposed by Victor and Purpura (1996), which has been also the most used in studies applying the discrimination analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the emphasis usually put on the spike train distances. In particular, the use of a metric specific for point processes like the Victor distance (Victor and Purpura, 1996) or a metric in an Euclidean space like for the binning distances is not so determinant for the discrimination performance as the classifier, given that in this case the binning procedure is not used to construct a high-dimensional space for the probability distributions (Strong et al, 1998). Notice that here we restricted ourselves to the type of classifier originally proposed by Victor and Purpura (1996), which has been also the most used in studies applying the discrimination analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To check to which degree binning is inconvenient by itself or becomes problematic only when used to construct a high dimensional R space (e. g. Strong et al, 1998), we also study a spike train distance based on binning (Schnupp et al, 2006). For each spike train, the spikes are binned in N B bins of width τ B .…”
Section: Binning Distance D Bmentioning
confidence: 99%
“…Current entropy rate estimation methods (e.g., Strong et al 1998) proceed by substituting the observed relative frequenciesp i for p i in Eq. 2, and subsequently extrapolating the finite l behavior of H (l)/l when l goes to infinite (i.e., when 1/l goes to 0).…”
Section: The Entropy Rate and The Lempel-ziv Estimatormentioning
confidence: 99%
“…The methods used to compute this measure are based on the difference between the response entropy rate H(R) and the response entropy rate given the stimulus H(R/S) and have been described in detail elsewhere (Strong et al, 1998;Chacron et al, 2001bChacron et al, , 2003a.…”
Section: Information Theory and Stimulus Estimationmentioning
confidence: 99%
“…The direct method of estimating information (Strong et al, 1998) will provide such an estimate. Alternatively, one can use the indirect method to obtain a lower bound on information transfer since this measure relies on linear decoding (Gabbiani, 1996;Rieke et al, 1996).…”
Section: Information Theory: Linear Versus Nonlinear Codingmentioning
confidence: 99%